Heavy metal nutrients in tomato plants cultivated in soil amended with biosolid composts - Melo, W. J. [UNESP]; Cintra, A. A D [UNESP]; Revoredo, M. D. [UNESP]; Braz, L. T. (My University, 2003)
The use of biosolids in horticulture could contribute to recycle residues produced by men. This study analyzed concentrations of Cu, Mn and Zn in the compost during fermentation, in the soil amended with the composts and in the tomato plant materials. Five composts were produced using sugar-cane bagasse, biosolid and cattle manure in the proportions: 75-0-25; 75-12.5-12.5; 75-25-0; 50-50- 0 and 0-100-0 (composts with 0; 12.5; 25; 50 and 100% biosolid), respectively. These composts were used in an experiment with 6 treatments (the 5 composts and a control with mineral fertilization) in a design of randomized blocks with a split plot design. The control and the treatment of 0% biosolid received inorganic nitrogen. All the treatments received the same amount of N, P and K. Two tomato plants were cultivated in each 24 L pot, in a greenhouse at the Technology Department of the Faculdade de Ciências Agrárias e Veterinárias of the Universidade Estadual Paulista in Jaboticabal County, São Paulo State, Brazil. The concentrations of Cu, Mn and Zn were evaluated in the compost 7, 27, 57, 97 and 127 days after composting began, in the soil 0 and 164 days after the compost applied, and in the plants. Compost, soil and plant samples were subjected to digestion with HNO3, H 2O2 and HCl and the metals were determined by AAS. There were positive and significant correlations between Mn in the compost and Mn uptake by the plant (0.46 p>0.05), and between Zn in the compost and Zn concentration in the plant (0.78 p>0.05). Cu, Mn and Zn concentrations increased during composting. The biosolid in the compost supplied Cu and Zn to tomato plants, and the cattle manure supplied Mn to the plants.
Keywords: Composting process; Cu; Lycopersicon esculentum mill.; Mn; Waste; Waste lycopersicon esculentum mill.; Zn